Screening of Fungi for Antimycobacterial Activity Using a Medium-Throughput Bioluminescence-Based Assay - Grey, Alexander B. J.; Cadelis, Melissa M.; Diao, Yiwei; Park, Duckchul; Lumley, Thomas; Weir, Bevan S.; Copp, Brent R.; Wiles, Siouxsie (Frontiers in Microbiology, 2021)
There is a real and urgent need for new antibiotics able to kill Mycobacteria, acid-fast bacilli capable of causing multiple deadly diseases. These include members of the Mycobacterium tuberculosis complex, which causes the lung disease tuberculosis (TB) as well as nontuberculous Mycobacteria (NTM) a growing cause of lung, skin, soft tissue and other infections. Here we describe a medium-throughput bioluminescence-based pipeline to screen fungi for activity against Mycobacteria using the NTM species M. abscessus and M. marinum. We used this pipeline to screen 36 diverse fungal isolates from the International Collection of Microorganisms from Plants (ICMP) grown on a wide variety of nutrient-rich and nutrient-poor media and discovered that almost all the tested isolated produced considerable anti-mycobacterial activity. Our data also provides strong statistical evidence for the impact of growth media on antibacterial activity. Chemical extraction and fractionation of a subset of the ICMP isolates revealed that much of the activity we observed may be due to the production of the known anti-mycobacterial compound linoleic acid. However, we have identified several ICMP isolates that retained their anti-mycobacterial activity in non-linoleic acid containing fractions. These include isolates of Lophodermium culmigenum, Pseudaegerita viridis, and Trametes coccinea, as well as an unknown species of Boeremia and an isolate of an unknown genus and species in the family Phanerochaetaceae. Investigations are ongoing to identify the sources of their anti-mycobacterial activity and to determine whether any may be due to the production of novel bioactive compounds.